Demonstration of a Temperature-Dependent Inactivating Factor of the Thermostable Direct Hemolysin in Vibrio parahaemolyticus - Takeda, Yoshifumi (1974)
A factor was found in Vibrio parahaemolyticus which inactivated the hemolytic activity of a purified, thermostable direct hemolysin. The inactivating factor was associated with the hemolysin but could be separated from it by diethylaminoethyl-cellulose column chromatography. The inactivating factor was activated by heating at 50 to 60 C, but was itself thermolabile and lost activity on heating to 70 to 100 C. The mechanism of the Arrhenius effect, observed with crude hemolysin of V. parahaemolyticus, is as follows. At 50 to 60 C, the temperature-dependent inactivating factor associated with hemolysin inactivates the hemolysin, whereas at 80 to 100 C the crude hemolysin retains activity because at this temperature the factor is inactivated.